We are what we eat : ethnic food and the making of Americans - Gabaccia, Donna R., 1949- (Harvard University Press, 1998)
Ghulam Bombaywala sells bagels in Houston. Demetrios dishes up pizza in Connecticut. The Wangs serve tacos in L.A. How ethnicity has influenced American eating habits - and thus, the make-up and direction of the American cultural mainstream - is the story told in We Are What We Eat. It is a complex tale of ethnic mingling and borrowing, entrepreneurship and connoisseurship, of food as a social and political symbol and weapon - and a thoroughly entertaining history of our culinary tradition of multiculturalism.